2018
DOI: 10.1007/s40121-018-0210-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV, HCV and HBV: A Review of Parallels and Differences

Abstract: Elimination of the three blood-borne viruses—human immunodeficiency virus (HIV), hepatitis B (HBV) and hepatitis C (HCV)—as public health issues may be plausible in the near future. Spectacular advances have been made with the introduction of highly effective antiviral agents into clinical practice, and prevention strategies are available for all three infections. Effective disease control, laid out by WHO global strategies, is currently feasible for all three viruses. However, for worldwide elimination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…This review summarizes currently available nucleos(t)ide-based drugs and their acyclic analogues that exhibit multi-target activity https://doi.org/10. 1016/j.ejphar.2019.172747 Received 28 June 2019; Received in revised form 16 October 2019; Accepted 17 October 2019 HIV, HBV and HCV are three blood-borne viruses that cause emerging infectious diseases in humans worldwide (Leoni et al, 2018). According to the WHO, viral hepatitis caused 1.34 million deaths in 2015, a number that is comparable to the number of annual deaths caused by tuberculosis and that is even higher than those attributed to HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review summarizes currently available nucleos(t)ide-based drugs and their acyclic analogues that exhibit multi-target activity https://doi.org/10. 1016/j.ejphar.2019.172747 Received 28 June 2019; Received in revised form 16 October 2019; Accepted 17 October 2019 HIV, HBV and HCV are three blood-borne viruses that cause emerging infectious diseases in humans worldwide (Leoni et al, 2018). According to the WHO, viral hepatitis caused 1.34 million deaths in 2015, a number that is comparable to the number of annual deaths caused by tuberculosis and that is even higher than those attributed to HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, HIV and HBV preventive strategies and treatment options are characterized by lifelong and chronic treatment, while for HCV, short-term and curative treatment is available. In contrast to HCV, for which a definitive cure has been developed because it does not persist in cells, the elimination of HBV and HIV infections worldwide is primarily hindered by their persistence in the host organism (Leoni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Early pre‐DAA HCV treatment relied mainly on interferon and ribavirin with SVR rates between 25% and 50%. In contrast, the novel DAA therapies result in SVR in >95% of all HCV patients 32 . Although our observational retrospective study design cannot infer causation, the improvements in re‐LT outcomes found in this study are likely a result of DAA therapy.…”
Section: Discussionmentioning
confidence: 68%
“… 22 More importantly, HBV is often co-infected with HCV and HIV, resulting in a significant public health and socioeconomic burden all over the world, especially in underprivileged countries and regions. 23 , 24 Thus, early and rapid detection of HBV in suspected patients is essential to control infection by this pathogen. To date, ELISA and real-time PCR have been developed to identify HBV in clinical samples.…”
Section: Discussionmentioning
confidence: 99%